Elevated plasma and vitreous levels of leucine‐rich‐α2‐glycoprotein are associated with diabetic retinopathy progression. Issue 3 (23rd November 2017) - Chen, Chong; Chen, Xia; Huang, Hengye; Han, Changjing; Qu, Yuan; Jin, Huiyi; Niu, Tian; Zhang, Yuan; Liu, Kun; Xu, Xun
Abstract: Purpose: To investigate the association of plasma and vitreous leucine‐rich‐α2‐glycoprotein (LRG1) with diabetic retinopathy (DR) progression. Methods: A total of 86 outpatients and 33 inpatients were recruited. Outpatients with type 2 diabetes mellitus (T2DM) were classified as T2DM without DR ( n  =   22), nonproliferative DR (NPDR) ( n  =   20) and proliferative DR (PDR) ( n  =   22) based on international clinical DR severity scales. A total of 86 plasma and 33 vitreous samples were collected and subjected to enzyme‐linked immunosorbent assay. The diagnostic value of plasma LRG1 was tested using receiver operating characteristic (ROC) curves. Results: Plasma LRG1 in PDR patients (9025 ± 1870 pg/ml) was significantly increased as compared with controls (5975 ± 2022 pg/ml), T2DM without DR (6550 ± 2359 pg/ml) and NPDR patients (6550 ± 2359 pg/ml) (p   <   0.0001). Vitreous LRG1 in PDR patients was elevated by approximately 4.3‐fold than that in controls (562.1 ± 273.5 ng/ml versus 130.0 ± 102.8 ng/ml, p   =   0.000). The area under the ROC curve value for plasma LRG1 was 0.786 (p   <   0.0001). The maximal Youden index was 0.4372 and the optimal cut‐off value of LRG1 was 7357.043 pg/ml with 81.82% sensitivity and 61.90% specificity. Conclusion: Plasma and vitreous LRG1 levels were elevated in patients with PDR. Leucine‐rich‐α2‐glycoprotein (LRG1) might be a potential risk‐warning marker for PDR.